PENINGKATAN KOSAKATA BAHASA INGGRIS MENGGUNAKAN TEKNIK DAFTAR KATA DAN MEWARNAI GAMBAR DENGAN GAMBAR AI DI SD INPRES TALONDO 1 - Hamzar Hamzar; Muhammad Ardiansyah; Aulia Tiara Cahyani; Matriadi Matriadi; Ahmed Absi; Abdurrahman Faris Indriya Himawan (Jurnal Abdi Insani, 2025)
This Community Service Journal is underlain by the obstacles faced by students (lack of motivation to learn English, lack of awareness of the momentousness of English, and poor vocabulary skills) and teachers (limited teaching materials, textbooks submitted to the Ministry not matching those received, lack of English teaching techniques, and inability to create teaching materials using AI) at Talondo 1 Elementary School, Tamalea Village, Bonehau Subdistrict, Mamuju Regency, West Sulawesi Province, Indonesia. This activity aims to elevate students' English vocabulary and determine their response to English vocabulary training using vocabulary lists and colouring pictures with AI images. The methods were mixed methods with an experimental and descriptive approach. The populations were 41 people, and the samples were 10 people. The sample collection technique employed purposive random sampling. The data collection techniques utilised observation, pre-tests, post-tests, and interviews. The activity was carried out over 2 meetings. The activity method used pre-tests, training, post-tests, and interviews. The results of this study pointed out that learning English vocabulary using vocabulary lists and colouring pictures with AI images ameliorated students' English vocabulary. When comparing the pre-test results (28.51) with the post-test results (50.76), it can be deduced that the students' vocabulary enhanced significantly, even though the training only lasted for two sessions. Students were also very delighted with the combination of the vocabulary list technique and the colouring technique with AI images. It is hoped that this vocabulary teaching technique can be applied as a reference for teachers to teach and advance students' vocabulary.